Dataset: The viscosity effect of TiO2 on soda‐lime‐silicate bearing glass - Karlsson, Stefan (RISE Research Institutes of Sweden, 2021)
As TiO2 is replacing SiO2 it has a slight suppressing effect on the viscosity until the limit when Na2O/TiO2 ratio is less than 2, indicating a transformation of the structure of TiO2, a remarkable increase in the fragility and viscosity is observed for the calculated low temperature region. The change is not as evident for the high‐temperature region. CaO replaced by TiO2 gives almost no effect on the viscosity, however, as it approaches Na2O/TiO2≈2 it tends to crystallize at temperatures of 1000‐1050 °C.

När TiO2 ersätter SiO2 har det en liten nedtryckande effekt på viskositeten. Tills gränsen när Na2O / TiO2-förhållandet är mindre än 2, vilket indikerar en transformation av strukturen för TiO2, då sker en anmärkningsvärd ökning av viskositetsbräckligheten observeras för den beräknade låga temperaturregion. Förändringen är inte lika tydlig för regionen med hög temperatur. CaO ersatt av TiO2 ger nästan ingen effekt på viskositeten, men när den närmar sig Na2O / TiO2≈2 tenderar den att kristallisera vid temperaturer på 1000-1050 ° C.
Dataset: Viskositetseffekt av TiO2 på soda kalk silikat glas
Keywords: THERMAL PROPERTIES; glass; glas; melting; smältning; thermodynamics; termidynamik; viscosity; viskositet; Geology; Geologi; Geophysics; Geofysik; Geochemistry; Geokemi; Materials Engineering; Materialteknik; Mineral and Mine Engineering; Mineral- och gruvteknik; Geoscientific Information; Geovetenskap